2018
DOI: 10.5210/fm.v23i11.9413
|View full text |Cite
|
Sign up to set email alerts
|

Communicative functions of emoji sequences on Sina Weibo

Abstract: The popular press is currently rife with speculation that emoji are becoming a global, digitally-mediated language. Sequences of emoji that function like verbal utterances potentially lend strong support to this claim. We employ computer-mediated discourse analysis to analyze the pragmatic meanings conveyed through emoji sequences and their rhetorical relations with accompanying text, focusing on posts by social media influencers and their followers on a popular Chinese social media platform. The findings show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 19 publications
7
51
0
2
Order By: Relevance
“…In addition, we have shown that emoji sequences can fulfill certain communicative functions that were previously associated only with verbal utterances [.]" (Ge, Herring 2018) This argumentation might be going even a bit too far, however, it still stresses the importance of further analyses of messenger communication such as the one proposed here, for there are vast areas of mobile communication that have not been under a linguistic magnifying lens to date.…”
Section: Previous Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, we have shown that emoji sequences can fulfill certain communicative functions that were previously associated only with verbal utterances [.]" (Ge, Herring 2018) This argumentation might be going even a bit too far, however, it still stresses the importance of further analyses of messenger communication such as the one proposed here, for there are vast areas of mobile communication that have not been under a linguistic magnifying lens to date.…”
Section: Previous Researchmentioning
confidence: 85%
“…This is even more so since WeChat with vigor shifts the frontiers of digitization and inevitably has become a model for Western societies' patterns of digital transformations (Szurawitzki 2018, 139-140). Ge, Herring (2018) even go so far as to suggest some very far-reaching tendencies in the emoji sequences they analyzed in Sina Weibo communication:…”
Section: Previous Researchmentioning
confidence: 99%
“…Sina Weibo, China's indigenous microblogging site, lends itself well to emoji sequence analysis. Emoji useincluding the formulation of emoji sequences -is common on Weibo due to the platform's emoji affordances and developed emoji culture [11,12]. In short, by focusing on China, whose culture fosters an especially high concentration of emoji use [11], this study advances current CMC and emoji literatures, while also providing new insights which can inform the future design of emoji and social media platforms.…”
Section: Introductionmentioning
confidence: 86%
“…The common occurrence of emoji sequences in computer-mediated communication (CMC), defined as "two or more emoji with different meanings that stand together to form a conceptual unit" [12, p.1], has led to the popular speculation that emoji are evolving into a new and digitally-mediated language [8,12]. Indeed, these colorful, cute and playful pictographs go beyond merely expressing emotions and embellishing messages; rather, a sequence of emoji can function as a sentence-like textual utterance (though it may not convey a complex idea or concept), offering social media users a new way of meaning-making, expression and selfpresentation [8,15,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation